THE INFLUENCE OF THE PRINCIPAL’S LEADERSHIP STYLE ON THE PERFORMANCE OF PUBLIC ELEMENTARY SCHOOL TEACHERS 5 AIR GEGAS - Adam, Handika Sopian; Hidayati, Dian (Universitas Pendidikan Indonesia, 2019)
The research aims to obtain data on (1) the principal's leadership style in improving work discipline, (2) the principal's leadership style in increasing teacher work motivation, (3) the principal's leadership style in increasing responsibility and (4) constraints that faced by principals in improving expected teacher performance. This study uses a qualitative approach with descriptive methods, the technique of data collection is done through in-depth interviews, observation, and documentation. This study shows that (1) principals apply democratic leadership styles in improving discipline, (2) principals apply developer leadership styles (builders) in increasing teacher work motivation, (3) principals apply executive leadership styles in increasing teacher responsibilities, and (4) constraints faced by the principal, namely the decline in teacher discipline, lack of teacher performance motivation, and a low sense of teacher responsibility in learning. It is recommended that the principal can apply a better or varied leadership style so that the desired goals can be achieved well and maximally.